Peran Kader dalam Pemanfaatan Buku KIA pada Masa Nifas: The Role of Cadres in Utilizing the KIA Book During the Pospartum Period - Winarso, Septerina Purwandani; Aini, Fajaria Nur; Hapsari, Wanodya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
One effort to reduce maternal and infant mortality is through the use of the KIA handbook. The use of the KIA handbook is a strategy for empowering communities, especially families, to maintain health and efforts to obtain quality services according to standards. Cadres are community motivators to be aware of maternal and child health. In the use of the KIA handbook, cadres play a crucial role in providing education to mothers and assisting midwives in monitoring the health conditions of mothers and their babies. Community service activities aim to increase cadres' knowledge about the use of the KIA handbook, especially during the postpartum period. The activity was carried out in Karangtengah Village, Baturraden District. Thirty-eight community service participants participated. The methods used included lectures, discussions, and question-and-answer sessions. The results of the community service showed that the level of knowledge among cadres before receiving education was mostly lacking (94.7%), while after receiving education, the majority had sufficient knowledge (65.8%).